Dandruff: The most commercially exploited skin disease - Ranganathan S (Indian Journal of Dermatology, 2010)
The article discuss in detail about the prevalence, pathophysiology, clinical manifestations of dandruff including the etio-pathology. The article also discusses in detail about various treatment methods available for dandruff. The status of dandruff being amphibious - a disease/disorder, and relatively less medical intervention is sought after for the treatment, dandruff is the most commercially exploited skin and scalp disorder/disease by personal care industries.